Human Pituitary Adenoma Proteomics: New Progresses and Perspectives - Zhan, Xianquan; Wang, Xiaowei; Cheng, Tingting (Frontiers in Endocrinology, 2016)
Pituitary adenoma (PA) is a commonly intracranial neoplasm that impacts on human health through interfering hypothalamus-pituitary-target organ axis systems. The development of proteomics gives great promises in clarification of molecular mechanisms of a pituitary adenoma and discovery of effective biomarkers for prediction, prevention, early-stage diagnosis and treatment of a PA. A great progress in the field of PA proteomics has been made in the past ten years, including (i) the use of laser capture microdissection, (ii) proteomics analyses of functional PAs (FPAs, such as prolactinoma), invasive and noninvasive nonfunctional PAs (NFPAs), protein post-translational modifications (PTMs) including phosphorylation and tyrosine nitration, NFPA heterogeneity, and hormone isoforms, (iii) the use of protein antibody array, (iv) serum proteomics and peptidomics, (v) integration of proteomics and other omics data, and (vi) proposal of multi-parameter systematic strategy for a PA. This review will summarize those progresses of proteomics in PAs, point out the existing drawbacks, propose the future research directions, and address the clinical relevance of PA proteomics data, in order to achieve our long-term goal that is use of proteomics to clarify molecular mechanisms, construct molecular networks, and discover effective biomarkers.